Periodization of Urban Development in the Golden Horde State - Bocharov Sergei G.; Maslovskiy Andrey N. (Археология евразийских степей, 2022)
The paper attempts to find regularities in the process of formation, development and disappearance of the towns of the Golden Horde State. The emergence of a large number of big and medium-sized towns in the Eastern European steppe in a short period by historical standards and their equally rapid disappearance is probably the most striking phenomenon in the history of the Golden Horde. This process largely depended on the evolution and well-being of the still understudied sedentary rural settlements. Seven periods in the history of urban development of the Golden Horde are defined, each having its characteristic features and regularities. On the whole, the process of foundation, development and disappearance of Golden Horde cities covered a chronological range of under two centuries from the 1240s to the 1420s.